2010
DOI: 10.1002/lsm.20960
|View full text |Cite
|
Sign up to set email alerts
|

In vitro investigation of the biological effects associated with human dermal fibroblasts exposed to 2.52 THz radiation

Abstract: Human dermal fibroblasts exhibit comparable cellular and molecular effects when exposed to THz radiation and hyperthermic stress. These findings suggest that radiation at 2.52 THz generates primarily thermal effects in mammalian cells. Therefore, we conclude that THz-induced bioeffects may be accurately predicted with conventional thermal damage models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 62 publications
3
79
0
2
Order By: Relevance
“…First, they provide high levels of average output power, with values on the order of 100 mW at many frequency lines. Notably, these power values are the highest levels of all commercially available bench-top THz sources [43,[119][120][121][122] (Fig. 5a).…”
Section: Direct Generation Laser Sourcesmentioning
confidence: 89%
See 2 more Smart Citations
“…First, they provide high levels of average output power, with values on the order of 100 mW at many frequency lines. Notably, these power values are the highest levels of all commercially available bench-top THz sources [43,[119][120][121][122] (Fig. 5a).…”
Section: Direct Generation Laser Sourcesmentioning
confidence: 89%
“…Exposure chambers are either custom built using stainless steel or plexiglass materials, or they are designed using conventional cell culture incubators. Figure 5b and c contain images of a retrofitted chamber using a cell culture incubator, and a custom-designed exposure chamber, respectively [120,145]. Chambers generally consist of an external heater, temperature controller, gas control and purging system, sapphire windows for IR measurements, operator control area, and input ports for THz radiation.…”
Section: Equipment Used For Controlled Exposures and Accurate Dosimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…22 However, heating effects could still be an issue, and so safe levels of exposure have been set in the milliwatt regime. [23][24][25] This level is orders of magnitude above the typical powers of pulsed terahertz systems, where common average output powers are reported to be on the order of 100 nW. 26 Intermolecular bonds, such as hydrogen bonds, have been found to have resonances extending into the terahertz region.…”
Section: Introductionmentioning
confidence: 96%
“…Work by Pickwell et al, has demonstrated that the terahertz response of normal human skin can be modeled in much the same way as water using a double Debye equation [4,5], furthermore, they also extract Debye parameters (Table 1) from the refractive index and absorption coefficient. Recently, Heh using the Debye parameters and alternating-direction-implicit Finite-difference timedomain (FADI-FDTD) modeled the interaction of terahertz pulse with healthy skin and basal cell carcinoma (BCC) [6].Recent studies [7,8] draw the attention of the potential therapeutic effect of THz in the field of cancer, which necessitates a better understanding of the interaction of terahertz pulse with healthy skin and BCC. …”
Section: Introductionmentioning
confidence: 99%